Conservatively treated Congenital Hyperinsulinism (CHI) due to K-ATP channel gene mutations: reducing severity over time - Salomon-Estebanez, Maria (Orphanet J Rare Dis, 2016)
BACKGROUND: Patients with Congenital Hyperinsulinism (CHI) due to mutations in K-ATP channel genes (K-ATP CHI) are increasingly treated by conservative medical therapy without pancreatic surgery. However, the natural history of medically treated K-ATP CHI has not been described; it is unclear if the severity of recessively and dominantly inherited K-ATP CHI reduces over time. We aimed to review variation in severity and outcomes in patients with K-ATP CHI treated by medical therapy. METHODS: Twenty-one consecutively presenting patients with K-ATP CHI with dominantly and recessively inherited mutations in ABCC8/KCNJ11 were selected in a specialised CHI treatment centre to review treatment outcomes. Medical treatment included diazoxide and somatostatin receptor agonists (SSRA), octreotide and somatuline autogel. CHI severity was assessed by glucose infusion rate (GIR), medication dosage and tendency to resolution. CHI outcome was assessed by glycaemic profile, fasting tolerance and neurodevelopment. RESULTS: CHI presenting at median (range) age 1 (1, 240) days resolved in 15 (71%) patients at age 3.1(0.2, 13.0) years. Resolution was achieved both in patients responsive to diazoxide (n = 8, 57%) and patients responsive to SSRA (n = 7, 100%) with earlier resolution in the former [1.6 (0.2, 13.0) v 5.9 (1.6, 9.0) years, p = 0.08]. In 6 patients remaining on treatment, diazoxide dose was reduced in follow up [10.0 (8.5, 15.0) to 5.4 (0.5, 10.8) mg/kg/day, p = 0.003]. GIR at presentation did not correlate with resolved or persistent CHI [14.9 (10.0, 18.5) v 16.5 (13.0, 20.0) mg/kg/min, p = 0.6]. The type of gene mutation did not predict persistence; resolution could be achieved in recessively-inherited CHI with homozygous (n = 3), compound heterozygous (n = 2) and paternal mutations causing focal CHI (n = 2). Mild developmental delay was present in 8 (38%) patients; adaptive functioning assessed by Vineland Adaptive Behavior Scales questionnaire showed a trend towards higher standard deviation scores (SDS) in resolved than persistent CHI [−0.1 (−1.2, 1.6) v −1.2 (−1.7, 0.03), p = 0.1]. CONCLUSIONS: In K-ATP CHI patients managed by medical treatment only, severity is reduced over time in the majority, including those with compound heterozygous and homozygous mutations in ABCC8/KCNJ11. Severity and treatment requirement should be assessed periodically in all children with K-ATP CHI on medical therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13023-016-0547-3) contains supplementary material, which is available to authorized users.